2021
DOI: 10.3390/axioms10040286
|View full text |Cite
|
Sign up to set email alerts
|

Foundations of Engineering Mathematics Applied for Fluid Flows

Abstract: Based on a brief historical excursion, a list of principles is formulated which substantiates the choice of axioms and methods for studying nature. The axiomatics of fluid flows are based on conservation laws in the frames of engineering mathematics and technical physics. In the theory of fluid flows within the continuous medium model, a key role for the total energy is distinguished. To describe a fluid flow, a system of fundamental equations is chosen, supplemented by the equations of the state for the Gibbs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 36 publications
0
57
0
5
Order By: Relevance
“…Connected equations (1) forming a parametrically and length scale-invariant system of coupled algebraic-differential equations is supplemented with physically based initial and boundary conditions. Consistency of the infinitesimal symmetries of the system (1) with the basic principles of physics [2] testifies to the validity of its choice as a universal basis for studying fluid flows. The complete solution of the system (1) is searched with the compatibility condition [2].…”
Section: G G P S T G T P S T T Pq Dtmentioning
confidence: 99%
See 3 more Smart Citations
“…Connected equations (1) forming a parametrically and length scale-invariant system of coupled algebraic-differential equations is supplemented with physically based initial and boundary conditions. Consistency of the infinitesimal symmetries of the system (1) with the basic principles of physics [2] testifies to the validity of its choice as a universal basis for studying fluid flows. The complete solution of the system (1) is searched with the compatibility condition [2].…”
Section: G G P S T G T P S T T Pq Dtmentioning
confidence: 99%
“…The total energy concept gives room to consider all the mechanisms for its transfer in a flow, including transfer with a local flow velocity and a group wave one, slow diffusion processes with a characteristic rate, and rather fast ones in the course of localized direct atomic-molecular interactions (for example, at the size of a molecular cluster upon free surface elimination in merging fluids [2]. )…”
Section: General Principles Of the Science Philosophymentioning
confidence: 99%
See 2 more Smart Citations
“…In [19], Chashechkin has tried to formulate a list of principles that substantiates the choice of axioms and methods for studying nature. He showed that the axiomatics of fluid flows are based on conservation laws in the frames of engineering mathematics and technical physics.…”
Section: Brief Overview Of the Contributionsmentioning
confidence: 99%